2019
DOI: 10.1002/ygh2.357
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and economic burden of patients with chronic liver disease and thrombocytopaenia receiving platelet transfusions during planned invasive procedures

Abstract: Summary Background Platelet transfusions (PT) are the standard of care for thrombocytopaenia in patients with chronic liver disease (CLD) who are at risk for bleeding when undergoing planned invasive procedures (PIP). In addition to PTs having short‐term effectiveness, PTs are associated with complications (transfusion‐associated circulatory overload [TACO], transfusion‐related acute lung injury [TRALI] and increased healthcare resource utilisation [HCRU]). Objective To characterise the clinical and economic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Studies have shown that platelet counts below 50 to 75 × 10 9 /L can be associated with a higher risk of bleeding in patients undergoing a range of invasive procedures, requiring platelet transfusions or other rescue therapies for bleeding, posing a substantial healthcare burden in these patients [ 8 , 10 , 51 54 ]. Recently, a pooled post hoc analysis of the lusutrombopag phase 2b, L-PLUS 1, and L-PLUS 2 studies found that patients treated with lusutrombopag without platelet transfusion demonstrated a trend toward fewer procedural and post-procedural bleeding events compared to patients receiving platelet transfusions plus placebo treatment [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that platelet counts below 50 to 75 × 10 9 /L can be associated with a higher risk of bleeding in patients undergoing a range of invasive procedures, requiring platelet transfusions or other rescue therapies for bleeding, posing a substantial healthcare burden in these patients [ 8 , 10 , 51 54 ]. Recently, a pooled post hoc analysis of the lusutrombopag phase 2b, L-PLUS 1, and L-PLUS 2 studies found that patients treated with lusutrombopag without platelet transfusion demonstrated a trend toward fewer procedural and post-procedural bleeding events compared to patients receiving platelet transfusions plus placebo treatment [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the need for pre-procedural platelet transfusions and rescue treatment for up to 7 days post procedure in patients with severe thrombocytopenia may have a significant positive impact on their healthcare resource utilization. As an oral treatment, given once a day for 7 days, lusutrombopag is simple to administer, and can be easily scheduled in advance of a planned procedure, a significant contrast to the resources an inpatient pre-procedural platelet transfusion would require, especially in a post-pandemic environment [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 A recent retrospective study of claims data found a mean payment increase of $11,100 (25%) in total costs for patients with CLD and thrombocytopenia who received platelet transfusions during a planned invasive procedure-related hospital admission and matched patients who did not receive transfusion. 23 The increased cost of platelet transfusions was attributed to increased resource utilization and lengths of hospital stay driven by a significant increase in bleeding events and acute respiratory failure. A 2013 AABB survey 24 reported 54 hospitals (10.5% of those surveyed) delayed elective surgeries due to unmet platelet needs, demonstrating that reliance on platelet transfusion can cause the postponement of procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the safety measure and proper use of the platelet preparations are complicated owing to their short lifetime and the difficulty in storage management in medical facilities [ 4 ]. Furthermore, the effects of PT on increasing platelet counts [ 5 ] and reducing bleeding events [ 6 ] remain uncertain.…”
Section: Introductionmentioning
confidence: 99%